GIS-material for the archaeological project: Scramasax, settlement and graves in Skälstad - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
During 2005 a preliminary investigation and a subsequent final excavation were performed on the archaeological sites RAÄ 1, 15 and 133 within the property Skälstad 1:2, Kvillinge parish in Norrköping. In the north-east part of the excavation area three rune stones are situated, of which one might stand in its original location. No features or finds were discovered nearby the rune stones, because the ground was very disturbed by cables and trenches. Earlier surveys have shown that the settlement site RAÄ 113 and the burial ground RAÄ 15 date to two separate time periods, namely the Early Iron Age and the Vendel era (Late Germanic Iron Age), and that the burial ground has to distinct main datings - the early and the late Vendel era. The excavation showed that one of the graves could be as old as from the late Migration period. The youngest dating from the burial ground was Viking age. No activities older than the settlement site, that is Early Iron Age, have been discovered. Probably the settlement site was turned into a burial site quite fast after the settlement had been deserted. The parts of the investigation area that could probably had been connected to the settlement were excluded from development and thus not investigated more thoroughly.
Only a few artefacts were found, which can be explained by the heavy ploughing carried out since the previous surveys. In one of the fire layers a relatively well-preserved scramasax was found. The dating of the sword corresponds with the dating of the cremation graves, and also shows that there were persons with special attributes living in the district during the Vendel era. The odd placing of the artefact suggests that the burial ceremony has been both complicated and probably very symbolic. Another observation is that well-preserved finds can be discovered underneath the over-ploughed features and deep down in the clay.

Purpose:

The information in the purpose is translated from the archaeological report:
The preliminary investigation had three purposes; to delimit the settlement site RAÄ 113 and the burial ground RAÄ 15, to investigate whether there were any older remains than what was earlier expected, in relation to the level above sea, and to determine a border for the rune stone site RAÄ 1. The purpose of the final excavation was to document and excavate the area that included the outermost parts of the settlement site RAÄ 113 and the burial ground RAÄ 15.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Under 2005 utfördes en arkeologisk förundersökning och en därpå följande särskild undersökning inom fornlämningarna RAÄ 1, 15 och 133 i Skälstad 1:2, Kvillinge socken i Norrköping. I undersökningsområdets nordöstra del står tre runstenar och av dessa står möjligen en på ursprunglig plats. Vid undersökningen påträffades inga anläggningar eller fynd i runstenarnas närhet eftersom marken var mycket omrörd av kablar och diken. Tidigare undersökningar har visat att boplatsen, RAÄ 133, och gravfältet, RAÄ 15, härrör från två olika perioder, äldre järnålder och vendeltid, och att gravfältet har två tydliga tyngdpunkter, en i äldre och en i yngre vendeltid. Vid undersökningen 2005 framkom att en grav skulle kunna kan vara så gammal som sen folkvandringstid. Den yngsta dateringen inom gravfältet var vikingatida. Det har inte gått att påvisa några aktiviteter som skulle vara äldre än tiden för boplatsen, det vill säga äldre järnålder. Det troliga är att marken där boplatsen låg mycket snart efter boplatsens upphörande övergick till att bli ett gravfält. De delar av undersökningsområdet som sannolikt hade kunnat knytas till boplatsen kom att undantas exploatering, varför de inte har undersökts närmare.
Bara ett fåtal fynd påträffades, något som kan förklaras av att marken hade brukats hårt sedan de tidigare undersökningarna. I ett av brandlagren framkom dock en relativt välbevarad scramasax. Svärdets datering stämde väl överens med brandgravarna och det visar dessutom att bygden under vendeltid bör ha haft vissa personer med speciella attribut. Fyndets udda placering antyder också att begravningsritualen varit komplicerad och säkert ytterst symbolbärande. En annan iakttagelse är att det kan förekomma välbevarade fynd under de sönderplöjda anläggningarna och djupt nere i leran.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Förundersökningen hade tre syften: Att avgränsa boplatsområdet RAÄ 133 och gravfältet RAÄ 15, att utreda huruvida det fanns äldre lämningar än tidigare förväntat i förhållande till nivån över havet och att bestämma begränsning för fornlämningsområdet tillhörande runstenarna, RAÄ 1. Den särskilda undersökningens syfte var att dokumentera och undersöka den yta som utgjorde den yttersta delen av boplatsen RAÄ 133 och gravfältet RAÄ 15.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Scramasax, boplats och gravar i Skälstad
Keywords: Iron Age; järnålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive